Electric field and space charge characteristics of xlpe insulation doped with nanofillers - Shaari, Jamil (2018)
Various types of nanoparticles had been introduced as additive to polymeric insulator by previous researchers. As a result, the existence of nanometre-size particles is well acknowledged in enhancing the dielectric strength in insulation material. The remained unanswered that is concerning the nanometre-sizes in maximising the potential of nanocomposite insulator. The main criteria to dictate the dielectric performance is by measuring the level of electric field distribution. While, electric field properties also influenced by the accumulation amount of space charge. So, this study was conducted to evaluate the electric field and space charge distribution in within nanocomposite insulator. The primary purpose is to identify the finest size in each type of selected nanoparticles in optimising the dielectric properties, but selecting the best type of nanofillers as well. Three different sizes attributed from 100nm, 80nm and 50nm were selected from three different nanofillers which are nanometre silicon dioxide (NSD), nanometre titanium dioxide (NTD) and air. All these nanofillers were doped in XLPE separately for simulation based study. Electric field distribution and space charge tabulation on each selected size were measured and compared. Consequently, each type of nanofillers give a selection different of sizes for the best dielectric performance. Conclusively, the best size for NSD, NTD and air were 100nm, 80nm and 50nm respectively. The dominant influence of nanometre-size is the intrinsic behaviour of an oxidised element in nanofillers. In term of type, NTD is performed in electric field distribution can correlated with its permittivity constant, ε. But for space charge tabulation, NSD is better due its intrinsic behaviour and insulation structure.